THE EFFECTIVENESS OF THE STEM APPROACH USING ECOMINI ON THE ECONOMIC LITERACY OF FIFTH-GRADE STUDENTS IN ECONOMIC ACTIVITIES - Windi Nurlaela Sari; Enjang Yusuf Ali; Kusman Rukmana (Universitas Majalengka, 2026)
The low level of economic literacy among elementary school students regarding economic activities indicates that instruction has not yet fully provided a learning experience that is contextual, active, and relevant to students’ daily lives. This study aims to analyze the improvement in students’ economic literacy through the application of the STEM approach using Ecomini (Economy Mini) a mini-scale simulation of economic activities designed to provide real-world learning experiences in the classroom and to compare its effectiveness with conventional teaching methods. This study employed a quasi-experimental method with a non-equivalent control group design, involving 62 students from two elementary schools in Conggeang Subdistrict: 32 students from SDN Cibubuan II as the experimental group and 30 students from SDN Narimbang I as the control group. Data were collected through pretests, posttests, and observations, then analyzed using descriptive and nonparametric statistics via the Wilcoxon, Mann-Whitney, N-Gain, and effect size tests. The results showed that the average pretest score of the experimental class increased from 51.50 to 88.84 on the posttest, while the control class increased from 51.97 to 68.27. The results of the Wilcoxon test for both classes showed a significance value of 0.000 < 0.05, while the Mann-Whitney test indicated a significant difference between the two classes with a significance value of 0.000 < 0.05. The N-Gain score for the experimental class was 77.16%, placing it in the effective category, while the control class scored 33.98%, placing it in the ineffective category. Furthermore, the effect size of 0.84 falls into the large category, indicating a strong impact of implementing STEM through Ecomini on students’ economic literacy. These findings confirm that the STEM approach via Ecomini is more effective than conventional instruction because it fosters more active, contextual, participatory, and meaningful economic learning for elementary school students.